Modelagem da demanda de água de abastecimento para a cidade de Pirassununga - SP - Silva, João Batista da (Universidade Federal de São Carlos, 2005)
Because it is a natural resource that is vital to animal and vegetable life, and considered a temporary resource, water must be used with responsibility, aiming at its protection and preservation so there is no lack of it in the near future. There are several factors that contribute to the scarcity of water, ranging from the lack of a conservationist policy to the lack of consumer awareness. Predicting the average water consumption based on historic data is an important tool to be used in the planning, in the estimate of the consumption and in the direction of the sanitation management. The objective of this work is to analyze and model the data on the urban water consumption in the city of Pirassununga, State of São Paulo, from 1993 to 2002. The explanatory variables used were: the number of inhabitants per connection, the marginal water price, the ‘per capita’ income per household (replaced by the next added value), the temperature, the precipitation and the relative humidity of the air. The method of consumption per connection, the method by unitary coefficient and the linear model of multiples coefficients were applied after the treatment and graphic analysis of the data. Although there was an increase of the total consumption of water, the consumption per connection presented a drop. The model that best explained the consumption function was that of multiple coefficients. Most of the explanatory variables used were significant and their coefficient signs were also the ones expected.
Keywords: Estimativa de consumo de água; Métodos e modelo; Consumo de água em m3/mês; Custo por metro cúbico; Análise de variáveis climatológicas; Papel do saneamento no Brasil; ENGENHARIAS